Implementasi Teknologi Blockchain dalam Perbankan Syariah: Peluang, Tantangan, dan Kesiapan Regulasi di Bank Syariah Indonesia - Muhammad Khofal (ARTHASASTRA : Journal of Economics and Business, 2026)
The rapid development of digital technology has encouraged Islamic banking institutions to adopt innovative systems capable of improving efficiency, transparency, and transaction security. One of the emerging technologies is blockchain, which has significant potential to support the digital transformation of Islamic banking in Indonesia. This study aims to analyze the opportunities and challenges of blockchain implementation in Bank Syariah Indonesia (BSI), particularly in terms of operational efficiency, regulatory readiness, and human resource capacity. The novelty of this research lies in its focus on the integration of blockchain technology within Islamic banking practices by combining technological, regulatory, and sharia perspectives in the context of Indonesia’s largest Islamic bank. This research employed a qualitative approach using literature study and policy analysis methods. Data were collected from scientific journals, official reports, financial regulations, and related policy documents concerning blockchain and Islamic finance. The findings indicate that blockchain technology has the potential to enhance transaction transparency, automate sharia-based contracts through smart contracts, reduce operational costs, and strengthen financial inclusion. However, its implementation still faces several challenges, including limited digital infrastructure, inadequate regulatory frameworks, low technological literacy, and the scarcity of human resources with expertise in both blockchain technology and Islamic finance. The study concludes that blockchain can become a strategic foundation for strengthening a more innovative, inclusive, and competitive Islamic banking system. Therefore, collaboration among regulators, financial institutions, and academics is necessary to support sustainable blockchain implementation in Indonesia’s Islamic financial sector.